Palestinian-Israeli Conflict on International Trade in the Suez Canal - Siti Aisyah Hamzah; Seniwati Seniwati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The Suez Canal has played a significant role in assisting and expediting the delivery of heavy goods on cargo ships from Asia to Europe, accommodating 12 percent of total global trade. The Suez Canal is a very important source of foreign currency for Egypt, a country that is still grappling with a variety of long-standing economic problems. Since October 2023, Yemen's Houthi group has been targeting ships in the Red Sea that it claims are connected to Israel in solidarity with Palestinians facing Israeli attacks in the Gaza Strip. This ongoing tension in the Red Sea not only impacts the Suez Canal, but also the maritime transportation market, trade movements, and international supply chains, as taking alternative routes means increasing shipping time and operating costs. Despite its important role as an international shipping lane, The Suez Canal has experienced a decline in status on the global stage due to various geopolitical events and economic crises that have occurred. This study aims to analyze the reciprocal relationship between international market dynamics and the strategic role of the Suez Canal. The chapter begins with an analysis of the impact of the Palestinian-Israeli conflict on international trade flows through the Suez Canal, followed by a discussion of the impact of the global economic crisis and conflict mitigation efforts on maritime security of shipping traffic. Finally, this chapter provides solutions that can be offered from the perspective of maritime security theory and international conflict theory.